Improvement of Harvesting Methods of Perennial Seed Grass (Agricultural Engineering, 2017)
In case of traditional harvesting methods the losses of perennial grass seeds may reach 45-50% of the biological yield in unfavourable weather conditions. The paper presents the results of comparative assessment efficiency of various methods of harvesting of perennial seed grass. It was found that the use of special devices and structures in combine harvesters allows increase of yield of technological mixture to the combine tank, degree of seed threshing to 93% and limit the losses of crop to 20-29%. Harvesting of seeds in non-waste technology with harvesting of the entire yield with later transport, drying, threshing and seeds cleaning in stationary devices results in reduction of losses by 5 to 10% but it leads to the increase of energy inputs by 24-25% in comparison to traditional with threshing method. Harvesting with a combing method of plant seeds on a trunk in „Невейки” technology results in the increase of the seeds harvesting to 86-98% of a biological yield.